2022
DOI: 10.1097/md.0000000000030474
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of 30-day mortality in patients with COVID-19 pneumonia under standard remdesivir and dexamethasone treatment

Abstract: Although some studies have reported prognostic factors for coronavirus disease 2019 (COVID-19), they were conducted before standard treatment with remdesivir and dexamethasone was implemented. This retrospective, observational study was conducted to evaluate various prognostic factors in patients with COVID-19 pneumonia receiving standard treatment with remdesivir and dexamethasone. Of 99 patients with COVID-19 pneumonia, 68 (68.7%) died within 30 days of hospitalization. The mean age was 71.3 years. Remdesivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 28 publications
2
9
2
Order By: Relevance
“…In Choi YJ et al's study, multivariate analysis confirmed that a high National Early Warning Score (NEWS) and Charlson Comorbidity Index (CCI) at admission, along with dyspnea, were independent risk factors for 30-day mortality in COVID-19 pneumonia patients treated with remdesivir and dexamethasone [60]. NEWS is based on a scoring system that combines six key physiological measurements (respiratory rate, SpO2, temperature, systolic blood pressure, heart rate, and level of consciousness) upon hospital admission or monitoring.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In Choi YJ et al's study, multivariate analysis confirmed that a high National Early Warning Score (NEWS) and Charlson Comorbidity Index (CCI) at admission, along with dyspnea, were independent risk factors for 30-day mortality in COVID-19 pneumonia patients treated with remdesivir and dexamethasone [60]. NEWS is based on a scoring system that combines six key physiological measurements (respiratory rate, SpO2, temperature, systolic blood pressure, heart rate, and level of consciousness) upon hospital admission or monitoring.…”
Section: Discussionmentioning
confidence: 93%
“…These identified factors provide valuable insights into the potential determinants of adverse outcomes associated with remdesivir use. In the realm of research on factors influencing the response to remdesivir in hospitalized patients with COVID-19, few studies have been conducted [60][61][62].…”
Section: Discussionmentioning
confidence: 99%
“…It is interesting to note that ethanol completely inactivates Mycoplasma According to a recent trial, introducing early antibiotic therapy for COVID-19 pneumonia had no positive effects on 30-day mortality [27]. Despite what was predicted [28,29], the authors [27] did not discover any appreciable vaccination benefit in reducing illness severity and death among patients with COVID-19 pneumonia. The GSS fell more in the Intervention group than in the control group, according to our findings, and these data reached a statistically significant level (p = 0.016).…”
Section: Discussionmentioning
confidence: 99%
“…The abnormal presence of Mycoplasma salivarium in the lower tract or the lack of Clostridia in the upper tract was linked to worse outcomes in ICU patients [24]. It is interesting to note that ethanol completely inactivates Mycoplasma According to a recent trial, introducing early antibiotic therapy for COVID-19 pneumonia had no positive effects on 30-day mortality [27]. Despite what was predicted [28,29], the authors [27] did not discover any appreciable vaccination benefit in reducing illness severity and death among patients with COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 standard treatment includes intramuscular dexamethasone and remdesivir [ 22 ]. A recent study has shown no benefit on the 30-day mortality from adding early antibiotic treatment for COVID-19 pneumonia [ 28 ]. Contrary to expectations [ 29 , 30 ], the authors [ 28 ] did not find significant vaccine effectiveness in lowering disease severity and mortality among patients with COVID-19 pneumonia.…”
Section: Discussionmentioning
confidence: 99%